Studies on Solute-Solvent Interaction of Different Concentrated Solutions of 3-Hydroxy-6-Chloro-8-Nitroflavanol in 70% Dioxane- Water and Methanol-Water by Viscosity Measurements - Raghuwanshi, P.B.; Doshi, A.G.; Narwade, M.L. (Asian Journal of Chemistry, 2010)
Viscosity measurements have been made on a system comprising 3-hydroxy-6-chloro-8-nitroflavanol in 70% dioxane-water and 70% methanol-water at 32ºC. The data have been used to calculate viscosity and B-coefficient. We have also studied the effect of solvent on the viscosity. It has been found that viscosity increases with increase in the percentage of dioxane and methanol. Also, viscosity increased due to increase in the concentration of 3-hydroxy-6-chloro-8-nitroflavanol (ligand solute) in case of solvent dioxane and decreased in case of solvent methanol.